ANALYSIS OF OPTIMAL MANUFACTURING METHOD FOR DISCRETE PARTS WITH THIN SECTIONS - NORAIMAN, WAN MUHAMMAD (IRC, 2017)
This report discusses the analysis of optimal manufacturing method for discrete parts with thin sections of a mechanical product known as the Slip-on Sprocket. The Slip-on Sprocket has many thin sections that were needed to be considered when needed to be manufactured to minimize defects or damages when the Slip-on Sprocket comes out from final manufacturing phases and eventually becomes the final product. This was because the slip-on-sprocket thin sections were hard to be manufactured properly causing the form fit function problem when the final product was done. Therefore, many manufacturing methods were considered and analyzed in order to solve the form fit function problem. Some of the manufacturing method involved were the type of the manufacturing method used in order to minimize this problem which was the investment casting process. Then, the manufacturing variables that were involved in the manufacturing method process were analyzed such as molten metal temperature, mold temperature, and ingate velocity of the molten metal. The variables were then furtherly optimized in order to manufacture the thin sections of the slip-on-sprocket properly. Software such as Click2Cast was used to calculate the value results output (Filling velocity, Filling time, Solidification Time, Solidification Porosity) that would be used later in the optimization phase. The calculated result were then inserted into Design Expert Software in order to optimize the manufacturing method variables values so that they would not conflict with each other too much. The optimized values of the manufacturing method variables were then validated through the simulation software. The optimized manufacturing method was successfully obtained by combining the best manufacturing method (investment casting) for the slip on sprocket and the optimization of the manufacturing variables which would yield the best manufacturing results